The Teacher and Students Relationships on Students' Engagement inside EFL Classroom - Maulidiyah, Ayu (RETAIN, 2021)
This research reports the study of teacher-students relationships in the classroom using qualitative research. He study focused on the impact of teacher-students relationships in English as a foreign language learning on students’ engagements based on the observation in the classroom of middle school. The results of this study revealed that some indicators of teacher-students relationships affect students’ behavioral, emotional, and cognitive engagement that enhance their interest in their learning process.